ТЕХНОЛОГІЯ ЗАСТОСУВАННЯ РІЗНИХ ВИДІВ МАСАЖУ В ПЕРШИЙ ПЕРІОД РОЗВИТКУ ТРОМБОЗА ГЛИБОКИХ СУДИН НИЖНІХ КІНЦІВ (Педагогіка вищої та середньої школи, 2010)
On the basis of results o f avto eksperymenta. the technology of the use of various prospects and receptions of massage is offered, with the purpose of acceleration of restoration processes after the total thrombosis of deep vessels of tower extremity.